Performance of honey bess (Apis mellifera L.) in three ecosystems in Laguna, Philippines - Fajardo, Analinda C. Manila (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2003)
The population growth rates, pollen spectra and honey produced in managed and unmanaged colonies of honeybees (Apis mellifera) were compared in three ecosysterns in Laguna Experiments were conducted at the Canlubang Industrial Estate, in the town of Bay and in the Makiling Forest Reserye representing the industrial, agricultural and forest environments, respectively, from August 30, 2000 to May 2002.